Social perception of others shapes one's own multisensory peripersonal space. (July 2018) - Pellencin, Elisa; Paladino, Maria Paola; Herbelin, Bruno; Serino, Andrea
Abstract: The perception of our self is not restricted to our physical boundaries, but it extends beyond the body to incorporate the space where individual–environment interactions occur, i.e., the peripersonal space (PPS). PPS is generally conceived as a low-level multisensory-motor interface mediating hand–object interactions. Recent studies, however, showed that PPS representation is affected by higher-level cognitive factors. Here we asked whether the multisensory representation of PPS is influenced by high-level mechanisms implied in social interactions, such as the social perception of others. To this aim, in Experiment 1, we developed and validated a new multisensory interaction task in mixed reality (i.e., the Social PPS task). This task allows measuring the boundaries of PPS between one self and another person in a fully controlled, yet highly ecological, set-up. In the Experiment 2, we used this task to measure how participants' PPS varied when facing another person. The social perception of this person was manipulated via a classic social psychology procedure, so that, in two conditions, she was perceived either as a moral or an immoral character. We found that PPS representation is sensitive to the social perception of the other, being more extended when participants were facing a moral than when facing an immoral person. This effect was specific for social context, as no change in PPS was found if participants were facing an object, instead of the person. Interestingly, the social manipulation affected also attitude, identification, willingness to interact with the other, so as interpersonal distance. Together these findings show that social perception of others affects both the psychological representation of the others in relation to oneself and the multisensory representations of the space between oneself and the other, offering new insights about the role of social cognition in body representation.